Food habits of the world's grey wolves - TM Newsome; L Boitani; G Chapron; P Ciucci; CR Dickman; JA Dellinger; JV López-Bao; RO Peterson; CR Shores; AJ Wirsing; WJ Ripple (2016)
Grey wolves Canis lupus have been studied extensively, but there has been no detailed review of the species' feeding ecology, despite growing debate about how to conserve wolf populations while limiting their impacts on wild or domestic ungulates. Here, we assess the extent to which the grey wolf diet varies among and within North America, Europe, and Asia. We derived dietary data from searches of published literature. We grouped studies based on their bioregional location. We compared grey wolf diet among locations using non-metric multidimensional scaling and analysis of similarity. We assessed whether increased human impacts are associated with decreased grey wolf dietary diversity. Finally, using studies from southern Europe, we assessed whether the importance of wild ungulates in grey wolf diet has increased over time, coincident with a decline in domestic species in grey wolf diet over time. We compiled dietary data from 177 studies incorporating 94607 scat and stomach samples. Grey wolf diet was dominated by large (240-650 kg) and medium-sized (23-130 kg) wild ungulates, but variation in the percentages of wild ungulates consumed, along with variation in the percentages of domestic and smaller prey species consumed, contributed to the dietary differences found among and within continents. We found no evidence that grey wolf dietary diversity varies globally, although the results from southern Europe suggest that grey wolves may switch their diets away from domestic species if more wild ungulates are available. The diversity of prey consumed by grey wolves shows that the species is capable of surviving dramatic anthropogenic upheaval. However, there is an urgent need to increase our understanding of grey wolf foraging ecology in human-dominated landscapes, in order to determine whether restoration of depleted prey populations, coupled with effective damage-prevention measures, will reduce human-wolf conflicts.